Technical note and clinical instructions for Acute Kidney Injury (AKI) in patients with Covid-19: Brazilian Society of Nephrology and Brazilian Association of Intensive Care Medicine - Suassuna,José Hermógenes Rocco (2020)
ABSTRACT We produced this document to bring pertinent information to the practice of nephrology, as regards to the renal involvement with COVID-19, the management of acute kidney injury cases, and practical guidance on the provision of dialysis support.As information on COVID-19 evolves at a pace never before seen in medical science, these recommendations, although based on recent scientific evidence, refer to the present moment. The guidelines may be updated when published data and other relevant information become available.